2019
DOI: 10.3389/fimmu.2019.01273
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Derived Suppressor Cells: Key Drivers of Immunosuppression in Ovarian Cancer

Abstract: The presence of tumor infiltrating lymphocytes (TILs) is associated with a longer overall survival in advanced stage epithelial ovarian cancer. Despite the prognostic impact of TILs, response to checkpoint-inhibitors and antigen-specific active immunotherapy is limited in ovarian cancer. The goal of our study was to investigate the interaction between ovarian cancer and the innate and adaptive immune system in the ID8-fLuc syngeneic ovarian cancer mouse model. For the in vivo experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 35 publications
2
63
1
Order By: Relevance
“…From a clinical point of view, this comparison is most relevant. In contrast to the focus on the adaptive immune system in ovarian cancer since 2003, this study clearly indicates a role for the innate immune system, as was also demonstrated by our group in an ovarian cancer mouse model 18. In subgroup analyses, a substantial role for the adaptive immune system seems to be maintained.…”
Section: Discussioncontrasting
confidence: 52%
“…From a clinical point of view, this comparison is most relevant. In contrast to the focus on the adaptive immune system in ovarian cancer since 2003, this study clearly indicates a role for the innate immune system, as was also demonstrated by our group in an ovarian cancer mouse model 18. In subgroup analyses, a substantial role for the adaptive immune system seems to be maintained.…”
Section: Discussioncontrasting
confidence: 52%
“…Overall, even though there is good outcome in some monotherapy trials blocking PD-1 or PD-L1 in EC (up to 57.1% ORR), a greater cohort of EC patients may benefit in combination therapy designs using ICI and other agents, which may potentially alleviate suppressor mechanisms in the tumor microenvironment (TME). Combination therapy has the potential to afford additive or synergistic benefits, as compared to single agent treatment, as well as to overcome resistance mechanisms that are observed with ICI monotherapy administration, due to the upregulation of alternative immune checkpoint molecules or to emerging resistance caused by the presence of cells such as myeloid-derived suppressor cells (MDSCs) [61][62][63][64][65]. Currently, several clinical trials are ongoing with ICI treatment in EC patients, which are used in combination with cytotoxic chemotherapy, other ICI, vaccines and other immunotherapies, or targeted therapies [25,26,29,32,66].…”
Section: Immune Checkpoint Blockade Therapy In Endometrial Cancermentioning
confidence: 99%
“…Additionally, myeloid-derived suppressor cells (MDSCs) enhance stemness and promote metastasis, induce resistance to therapy, and limit the anti-tumor functions of T cells through MDSC signature molecules, nitric oxide (NO), and arginase-1 (Arg-1) [91,92]. Elevated MDSC numbers are highly associated with resistance to conventional and novel therapies [61,62,93].…”
Section: Parameters Influencing the Response Of Ovarian Cancer To Immmentioning
confidence: 99%
“…However, most data in this regard exist on the adaptive immune system [8,9]. Nevertheless, our group recently provided evidence on the importance of the innate immune system in ovarian cancer [10,11]. The major players within this innate immune system are dendritic cells, myeloid derived suppressor cells, and macrophages.…”
Section: Introductionmentioning
confidence: 99%